(untitled) (Bangladesh Journal of Medical Microbiology, 2020)
Brucellosis is a major Bacterial Zoonotic disease worldwide. More than 500,000 new cases are reported globally every year with the annual incidence rates varying widely from <2 to >500 per 1000,000 population among different region of the world. This cross sectional descriptive study was carried out in the department of microbiology, Mymensingh medical college, Mymensingh, Bangladesh from 1st January to 31 December 2017, on total 600 patients of PUO with or without occupational exposure. Blood was taken as sample, serum was separated and screening test was done by Brucella specific latex agglutination test from all collected samples. A Titer of ≥ 1:160 was taken as positive. ICT, PCR and real time PCR were done from all screening positive samples. Among the study population 65.83% (395/600) were male and 34.17% (205/600) were female. The sero prevalence of Human Brucellosis was found 13.33% (40/300) and 5% (15/300), respectively in risk and non risk group of population. Out of 55 Brucella specific latex agglutination test positive samples 27.27% (15/55) were ICT positive, 5.45% (3/55) were PCR positive and 3.64% (2/55) were real time PCR positive. No ICT, PCR or Real time PCR cases were found from sero negative samples. Among the ICT positive cases 86.67% (13/15) from risk group and 13.33% (2/15) from non risk group of study population. Among the 3 PCR positive cases 13.33% (2/15) were from ICT positive cases and 2.5 % (1/40) from ICT negative cases. All PCR and Real time PCR positive cases were found in risk group of study population. No reliable data for Human Brucellosis is available in our country. However the present study revealed that a considerable number of Human Brucellosis is present in risk group as well as non risk group of population in both rural and urban area in Mymensingh district of Bangladesh. In our country we use only Brucella specific latex agglutination test for diagnosis of human Brucellosis. It is a non specific test and gives many false positive results. So it is necessary to introduce newer tests with higher sensitivity and specificity which will help to diagnose the disease rapidly and more accurately. Bangladesh J Med Microbiol 2020; 14 (2): 19-24